2017
DOI: 10.1007/s13280-017-0902-1
|View full text |Cite
|
Sign up to set email alerts
|

Balancing ecosystem function, services and disservices resulting from expanding goose populations

Abstract: As goose populations increase in abundance, their influence on ecological processes is increasing. We review the evidence for key ecological functions of wild goose populations in Eurasia and North America, including aquatic invertebrate and plant propagule transport, nutrient deposition in terrestrial and aquatic ecosystems, the influence of goose populations on vegetation biomass, carbon storage and methane emission, species diversity and disease transmission. To estimate the implications of their growing ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 164 publications
(208 reference statements)
0
37
0
1
Order By: Relevance
“…Relationships were generally in the expected direction with, for example, stronger mutualism values, weaker domination values, and more positive emotions associated with higher acceptance. However, as suggested by Buij et al (2017), the evaluation of ES and EDS is to some extent subjective. Results revealed that beliefs about ES did not form a coherent measure, but could be divided into nature versus food/ hunting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships were generally in the expected direction with, for example, stronger mutualism values, weaker domination values, and more positive emotions associated with higher acceptance. However, as suggested by Buij et al (2017), the evaluation of ES and EDS is to some extent subjective. Results revealed that beliefs about ES did not form a coherent measure, but could be divided into nature versus food/ hunting.…”
Section: Discussionmentioning
confidence: 99%
“…Geese provide various benefits to humans (i.e., ecosystem services) such as nutrient cycling and stimulation of plant productivity, recreational hunting, meat, esthetic experience, and ecotourism (Green & Elmberg, 2014). However, the super-abundance of some geese has also led to over-grazing and impacts on ecosystems, and it is associated with several "ecosystem disservices," such as crop damage, fouling on beaches and in parks, compromised air safety, contamination of freshwater, degradation of natural vegetation, and concern about spread of disease (Bakker et al, 2018;Buij et al, 2017;. Notably, what constitute a service or disservice partially depends on who makes the evaluation leading to different assessments by stakeholder groups (Buij et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While further research should test the generality of this phenomenon across a wide range of contexts, this could have significant impacts on ES research and policy. This 'EDS-biased behavior' hypothesis implies that the lack of awareness on ES may not be the main driver of nature-unfriendly behaviors, contrary to a widely accepted view (Buij et al, 2017;Shapiro and Báldi, 2014). To encourage nature-friendly societies, targeting EDS reduction may be more effective than targeting ES increase.…”
Section: Stakeholders' Actions May Be More Influenced By Eds Than By Esmentioning
confidence: 98%
“…Buij et al (2017) review the current knowledge of such ecosystem impacts, showing that impacts on other species can arise not just directly through changes to habitat composition but also indirectly via changes to the physical structure of habitats. They note that negative impacts on natural environments increase particularly when formerly migratory geese become year-round residents (as for barnacle geese Branta leucopsis in many European countries), and/or where birds occur in significantly higher densities than traditionally occurred as a consequence of use of farming landscapes.…”
Section: Current Conflictsmentioning
confidence: 99%